PERAN DEWAN PENGAWAS SYARIAH PADA LEMBAGA KEUANGAN SYARIAH DI INDONESIA - Sultoni, Hasan (EKSYAR: Jurnal Ekonomi Syari'ah & Bisnis Islam, 2019)
The Sharia supervisory board is a Shariah expert appointed by the General Meeting of shareholders on the recommendation of the Indonesian Ulama Council (MUI), with the task of providing advice and advice to the board of directors and supervising the company's activities in accordance with Sharia principles.This research serves to determine the role of Sharia supervisory board on sharia financial institutions in Indonesia. The method of research used is the library research method by studying the reference book and previous research results.The results showed that the role of the Sharia supervisory board was to ensure and supervise the suitability of the bank's operational activities against the fatwa issued by the National Sharia Council.